Full-cross-section deformation characterization of Cu/Al bimetallic tubes under Rotary-Draw-Bending based on physics-driven B-spline curves fitting. (March 2022) - Fu, Mengyu; Wang, Zili; Zhang, Shuyou; Liu, Xiaojian; Lin, Yaochen; Wang, Le
Graphical abstract: Highlights: Physics-driven B-spline curves well fit the full-cross-section deformation characteristics. Elongation percentage is considered in the cross-section fitting theory. Profile overflow and angle-shaped circumferential distortion appear on the deformed cross-section. Full-cross-section deformation is more significantly affected by outer wall-thickness than inner wall-thickness. Abstract: It is difficult to detect the inner layer of the bimetallic tube and to describe its full-cross-section deformation, which negatively affects its verification and utility. To tackle this issue, a novel theory is proposed for fitting the full-cross-section deformation characterization of Cu/Al bimetallic tubes under Rotary-Draw-Bending. The cross-section profiles on the bending outside are fitted by the physics-driven B-spline curves. The geometric characteristics and the bending principles are set as the physics information and drive the design of the control vertices of the fitting B-curves. The interlaminar shape inheritance of the bimetallic tube is implemented by the same position angle of the corresponding control vertices. The cross-section profiles on the bending inside are fitted by the regular curves considering the elongation percentage. The comparison between the theoretical profiles and the experimental profiles shows remarkable agreement. The average circumferential errors of the theoretical profiles are within 1.82%, far smaller than the errors of the traditional ovalization profiles. Additionally, the representative parameters of full-cross-section deformation are differently affected by the wall-thickness. The wall-thinning of the outer layer and inner layer usually shows an opposite tendency when the wall-thickness varies.